Intellectual Capital, Innovation Capability, Knowledge Integration of Hi-Tech firms in Thailand - Kenikasahmanworakhun, Phatthararuethai; Jinain, Papraporn; Khantanapha, Napaporn; Thanathanchuchot, Thanadat; Thanathanchuchot, Thanakorn; Channuwong, Sukhumpong (Journal of Neonatal Surgery, 2025)
Innovation is a crucial strategic component that enables firms to gain a sustainable competitive advantage and achieve long-term success. This research aimed to 1) examine the relationships between human capital, organizational capital, relational capital, and knowledge integration effect on innovation capability of Hi-Tech firms; 2) determine knowledge integration play the mediating role impact between human capital, organizational capital, relational capital on innovation capability of Hi-Tech firms in Bangkok, Thailand. This study used a quantitative research method to fully utilize the advantages of answer the research questions more comprehensively. Population was executive from to 10 Hi-Tech in Bangkok and sample 280 respondent via on simple random sampling, Statistic analyze by SEM. The research reveals that 1. human capital, organizational capital, relational capital, and knowledge integration positive effect on innovation capability 2) knowledge integration play the mediating role impact between human capital, organizational capital, relational capital on innovation capability of Hi-Tech firms in Bangkok, Thailand. These study results had various theoretical, practical, and policymaking implications as discussed by the authors